Wavelet Numerical Solutions for a Class of Elliptic Equations with Homogeneous Boundary Conditions - Jinru Wang; Wenhui Shi; Lin Hu (Mathematics, 2021)
This paper focuses on a method to construct wavelet Riesz bases with homogeneous boundary condition and use them to a kind of second-order elliptic equation. First, we construct the splines on the interval <semantics>[0,1]</semantics> and consider their approximation properties. Then we define the wavelet bases and illustrate the condition numbers of stiffness matrices are small and bounded. Finally, several numerical examples show that our approach performs efficiently.